“Análisis de los cursos permanentes de la casa de la cultura Benjamín Carrión núcleo de Chimborazo en el imaginario colectivo de los jovenes de 15 a 25 años, en el periodo julio – diciembre de 2016” - Johana Patricia, Asqui Palmay (2017)
The objective of the present research entitled "Analysis of the permanent courses of the House of Culture Benjamin Carrion nucleus of Chimborazo in the collective imagination of the young people of 15 to 25 years, in the period July - December of 2016", has as Main objective to analyze how the permanent courses dictated affect the collective imaginaries of the youth, the techniques that were used was the interview and the surveys that allowed to reach the respective conclusions, the applied instruments were the guides of questionnaires the same that allowed to know If the permanent courses dictated by the institution contributed to the diffusion of the local culture, the applied methodology allowed to arrive at the logic of the scientific knowledge with respect to the culture and collective imaginaries, the design of the research allowed to establish the plan and structure to obtain Answers to study questions, type of research Applied and descriptive through it was recorded, analyzed and interpreted the results obtained through the instruments, the population to which the instruments were applied was 382, young people aged 15-25 years and 6 directors of the Institution, we can conclude by saying that the permanent courses of the House of Culture located de Chimborazo influenced the collective imagination of young people through the courses diffuses the set of myths, forms, symbols, types, motifs or figure that characterizes To the society of the province of Chimborazo. The objective of the present research entitled "Analysis of the permanent courses of the House of Culture Benjamin Carrion nucleus of Chimborazo in the collective imagination of the young people of 15 to 25 years, in the period July - December of 2016", has as Main objective to analyze how the permanent courses dictated affect the collective imaginaries of the youth, the techniques that were used was the interview and the surveys that allowed to reach the respective conclusions, the applied instruments were the guides of questionnaires the same that allowed to know If the permanent courses dictated by the institution contributed to the diffusion of the local culture, the applied methodology allowed to arrive at the logic of the scientific knowledge with respect to the culture and collective imaginaries, the design of the research allowed to establish the plan and structure to obtain Answers to study questions, type of research Applied and descriptive through it was recorded, analyzed and interpreted the results obtained through the instruments, the population to which the instruments were applied was 382, young people aged 15-25 years and 6 directors of the Institution, we can conclude by saying that the permanent courses of the House of Culture located de Chimborazo influenced the collective imagination of young people through the courses diffuses the set of myths, forms, symbols, types, motifs or figure that characterizes To the society of the province of Chimborazo.